ANALISIS HIGHEST AND BEST USE TERHADAP ASET TETAP NON OPERASIONAL PEMERINTAH KABUPATEN NGAWI ( Studi Pada Lahan Bekas Terminal Lama Tahun 2011 ) - , Andri Sulistyo Wilantono, S.T.; , Dra. Wahyu Hidayati., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The highest and best use research for the non operational fixed asset which owned by the Government of Ngawi Regency at Dr. Rajiman street of, conducted with analysis of property productivity in law aspect, regulation and also aspect of physical and location using the threshold testing and rating grid so it can be obtained a possible alternative usage. Thus, conducted with supply and demand market analysis, and also finance feasibility analysis for each usage proposal. In this research, the data to be analyzed consist of primary data secondary data. Primary data containing the room rate, Sales price of ruko, Shop rental rate, futsal and badminton space rental rate, and expenditure that raised to be an alternative size measure, treadâs form, topography, utility and others was obtained through direct observation. Secondary data was obtained from Statistical Center Organization (BPS), PHRI and governmentâs institutions in Ngawi Regency. From the result of the analysis was gained three competent and possible farm usage proposal that is the use of hotel, ruko and rental sport centre. Based on the indicator of finance feasibility by Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), and Benefit Cost Ratio (BCR), thus, the use of hotel to be better indicated comparing to ruko and sport centre so that can be concluded that the alternative using of hotel represent the most optimal.